Inhibition of A5 Neurons Facilitates the Occurrence of REM Sleep-Like Episodes in Urethane-Anesthetized Rats: A New Role for Noradrenergic A5 Neurons? - Fenik, Victor B.; Marchenko, Vitaliy; Davies, Richard O.; Kubin, Leszek (Frontiers in Neurology, 2012)
When rapid eye movement (REM) sleep occurs, noradrenergic cells become silent, with the abolition of activity in locus coeruleus (LC) neurons seen as a key event permissive for the occurrence of REM sleep. However, it is not known whether silencing of other than LC noradrenergic neurons contributes to the generation of REM sleep. In urethane-anesthetized rats, stereotyped REM sleep-like episodes can be repeatedly elicited by injections of the cholinergic agonist, carbachol, into a discrete region of the dorsomedial pons. We used this preparation to test whether inhibition of ventrolateral pontine noradrenergic A5 neurons only, or together with LC neurons, also can elicit REM sleep-like effects. To silence noradrenergic cells, we sequentially injected the alpha2-adrenergic agonist clonidine (20-40 nl, 0.75 mM) into both A5 regions and then the LC. In 2 rats, successful bilateral clonidine injections into the A5 region elicited the characteristic REM sleep-like episodes (hippocampal theta rhythm, suppression of hypoglossal nerve activity, reduced respiratory rate). In 5 rats, bilateral clonidine injections into the A5 region and then into one LC triggered REM sleep-like episodes, and in 2 rats injections into both A5 and then both LC were needed to elicit the effect. In contrast, in 3 rats, uni- or bilateral clonidine injections only into the LC had no effect, and clonidine injections placed in another 6 rats outside of the A5 and/or LC regions were without effect. The REM sleep-like episodes elicited by clonidine had similar magnitude of suppression of hypoglossal nerve activity (by 75%), similar pattern of hippocampal changes, and similar durations (2.5-5.3 min) to the episodes triggered in the same preparation by carbachol injections into the dorsomedial pontine reticular formation. Thus, silencing of A5 cells may importantly enable the occurrence of REM sleep-like episodes, at least under anesthesia. This is a new role for noradrenergic A5 neurons.